Deconstructing the palm oil industry narrative in indonesia: Evidence from Riau province - Tyson, Adam; Varkkey, Helena; Choiruzzad, Shofwan Al Banna (Institute of Southeast Asian Studies, 2018)
Indonesia is the leading global producer of crude palm oil. Mass production of palm oil requires large-scale land conversion, resulting in Indonesia having the world’s highest rate of annual primary forest loss. Given the contentious nature and scale of palm oil production, this article considers Indonesia as a variant of the developmental patrimonialism model often applied to African countries. Developmental patrimonialism in the Indonesian context suggests that state power — expressed through various discourse and policy coalitions — favours palm oil companies and seeks legitimation through claims about national economic benefits. This development model may lead to absolute poverty reduction, employment and tax revenue, but can also produce inequality, resource dependencies and environmental degradation. From the authors’ observations in Riau province, there is a mismatch between the national narrative of palm oil as a force for good and the conspicuous underinvestment in public services and infrastructure, which undermines the legitimacy of some palm oil industry claims. The complexity of village Riau casts further doubt on generalized claims about rural development. Local variance in Riau’s palm oil belt is attributed to, among other things, the complex nature of political patronage, uneven access to land, volatile pricing trends, problematic financing and loan schemes, and the role played by village cooperatives.